The ranging behaviour of male barn owls as biological control agents of rats in Subang Jaya - Zabidi, Muhamad Amin (2016)
Barn owl has been established as biological control agents of rats in oil palm plantation and rice field. In view of the increasing rat infestation in the urban area, an attempt is made to introduce barn owl in this area. Subang Jaya has been chosen for the first release of barn owls for this purpose. Using radio telemetry the movement of barn owl was followed over a period of time. The objective is to determine the home range size and core area of male barn owls in a newly introduced area and also to investigate male explatory behavior in a newly introduced area. Two males barn owls and will be harnessed with a radio transmitter and tracked in the evening from 6 p.m to 6 a.m. Tracking data will be collected for at least 5 nights in month. The hourly distanced travelled will reflect the activity levels over the time interval. This will enable the plotting of levels of activity over the duration the owls were followed. The Biotas software will be used to analysed the data. The male barn owls is the bigger home range size and in a newly introduced